Sea Fence as Moral Battlefield: Local Media Framing and Religious Narratives in Banten’s Coastal Resistance - Mukhroman, Iman (Future Science, 2025)
This study analyzes how local online media framed religious narratives in the coastal social movement that rejected the construction of a sea fence on the north coast of Banten in mid-January 2025. Using a qualitative approach and Robert Entman's framing analysis method, this study examines the news coverage of two local online media, Kabar Banten online and Radar Banten online. The results of the analysis show differences in framing emphasis between the two. Kabar Banten tends to highlight the ecological dimension and legal violations of the installation of the sea fence by unknown actors, while Radar Banten emphasizes more on the aspects of social injustice and community and student solidarity as a form of resistance to the state and corporations. Both recommended the removal of the sea fence, but with different moral and political justifications. The findings show that media framing not only reflects social reality, but also produces meanings that influence public opinion and legitimize collective action. This research emphasizes public participation in marine space policy, media literacy, and the role of local media in policy conflicts, and opens up further studies on media and conflict in coastal Indonesia.